The oddity effect drives prey choice but not necessarily attack time. (5th June 2018) - Penry‐Williams, Iestyn L.; Ioannou, Christos C.; Taylor, Martin I.
Abstract: The tendency of predators to preferentially attack phenotypically odd prey in groups (the oddity effect) is a clear example of how predator cognition can impact behaviour and morphology in prey. Through targeting phenotypically odd prey, predators are thought to avoid the cognitive constraints that delay and limit the success of attacks on homogenous prey groups (the confusion effect). In addition to influencing which prey a predator will attack, the confusion and oddity effects would also predict that attacks on odd prey can occur more rapidly than attacking the majority prey type, as odd prey are more easily targeted, but this prediction has yet to be tested. Here, we used kerri tetra fish, Inpaichthys kerri, presented with mixed phenotypic groups of Daphnia dyed red or black to investigate whether odd prey in groups are preferentially attacked and whether these attacks were faster than those on the majority prey type. In agreement with previous work, odd prey were targeted and attacked more often than expected from their frequency in the prey groups, regardless of whether the odd prey was red in a group of black prey or vice versa. However, no difference was found in the time taken to attack odd vs. majority prey items, contrary to our predictions. Our results suggest that the time taken to make an attack is determined by a wider range of factors or is subject to greater variance than the choice of which prey is selectively targeted in a group.